Academic responsability in our time - Karchmer K, Samuel (Revista Universidad de Guayaquil, 2010)
Author states an all over ethical, moral, academic and professional medical crisis of values. It registers his criteria about the origin of this change and calls to a review of human behavoir and proceedings as members of scientific institutions which usually complete their academic requirements however ethical paradigms are far away to be reached